ASSESSMENT OF WORKPLACE DIFFICULTIES FACED BY NURSES WORKING IN TERTIARY CARE HOSPITAL - ASHRAF , F; JAN , I; ZAIB , A (Biological and Clinical Sciences Research Journal, 2024)
Occupational stress among nurses in government hospitals is a significant concern, impacting individual well-being and patient care quality. This study aimed to assess the prevalence of stress and its contributing factors among nurses in three government hospitals. This study aimed to evaluate the prevalence of stress among nurses in government hospitals and identify the factors contributing to their stress levels. A cross-sectional study involved 400 nurses from tertiary care Hospital. Demographic and workplace data were collected using a self-administered questionnaire, and stress levels were assessed using the Modified Expanded Nursing Stress Scale (ENSS). Most participants were female (70%) and aged between 25 and 35 (55%). Sixty per cent of nurses held a Bachelor's degree, and 40% had a diploma in nursing. Heavy workload was the most common stressor reported (70%), followed by long working hours (60%) and poor working relationships (45%). Binary logistic regression analysis revealed that female nurses were 1.5 times more likely to experience stress than males (p < 0.05). Nurses working more than 40 hours per week had a 1.3 times higher likelihood of experiencing stress (p < 0.05), and those with less than six years of job experience were 1.8 times more likely to report stress (p < 0.05). The study highlights a high prevalence of stress among nurses in government hospitals, primarily attributed to heavy workloads, long working hours, and poor working relationships. Addressing these factors through targeted interventions is crucial to improving the well-being of nurses and enhancing patient care quality.